2017
DOI: 10.3126/jnps.v37i1.17201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Drug Compliance in Paediatric Asthma

Abstract: Introduction: Childhood asthma is an immensely important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…In addition, McCorkle [27] and Baiardini et al [30] revealed that socioeconomic status and level of education markedly influences the way in which patients take their treatment. On the other hand, Singh et al concluded that 47 % of patients were compliant [31] . Compliance was associated with asthma severity while mother's education did not have any influence on the compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, McCorkle [27] and Baiardini et al [30] revealed that socioeconomic status and level of education markedly influences the way in which patients take their treatment. On the other hand, Singh et al concluded that 47 % of patients were compliant [31] . Compliance was associated with asthma severity while mother's education did not have any influence on the compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In Sin et al, [34] asthma knowledge had significant positive relationships with asthma selfmanagement behaviors and accounted for 14% of self-management behaviors variability. In addition, Singh et al [31] found that compliance was affected by total knowledge score. CONCLUSION In the present study, there were lack of asthma self-management knowledge and compliance.…”
Section: Discussionmentioning
confidence: 99%